From research to practice: a multifaceted and dimensional approach to psychopathy. Issue 4 (24th September 2021) - Steinert, Steven W.; Shankar, Sneha; Arble, Eamonn P.
Abstract : Purpose: This paper aims to evaluate trends in research and clinical practice that may contribute to the limited utility of assessment and treatment modalities designed to capture and address psychopathy. It identifies a lack of consistency between the academic understanding of psychopathy and how the construct is applied in clinical contexts. The authors provide clarity and direction for a more effective application of the psychopathy construct in practical contexts. Design/methodology/approach: This review first examines the etiology of important limitations to psychopathy research and practical application, and proposes the adoption of the most recent empirical conceptualization of the construct into practical contexts. It then evaluates the current functionality of psychopathy in practical contexts. The review ultimately proposes a method for designing intervention practices based on the model used in the development of dialectical behavior therapy (DBT) for borderline personality disorder, which will improve the practical utility of the construct. Findings: The present review provides evidence that a multifaceted and dimensional perspective of psychopathy will improve the practical utility of the construct and help move the field forward. It suggests that considering independent components of the psychopathy construct along a continuous scale, as with DBT, will contribute to improvements in assessments and treatments that target psychopathy. Practical implications: The current review applies relevant research to a model for developing an intervention modality particularly in forensic or correctional settings where individuals high in psychopathy are often seen. The implications outlined provide a framework that could impact practice and assessment in forensic contexts moving forward. Originality/value: Previous research has not concisely outlined problems concerning the link between psychopathy research and how the construct is applied in practical settings. Few researchers have proposed plausible solutions that could improve the utility of the construct in such settings.